HER2-mediated enhancement of Ebola virus entry - Kuroda, Makoto; Halfmann, Peter; Kawaoka, Yoshihiro (PLoS pathogens, 2020)
Multiple cell surface molecules including TAM receptors (TYRO3, AXL, and MERTK), a family of tyrosine kinase receptors, can serve as attachment receptors for Ebola virus (EBOV) entry into cells. The interaction of these receptors with EBOV particles is believed to trigger the initial internalization events that lead to macropinocytosis. However, the details of how these interactions lead to EBOV internalization have yet to be elucidated. Here, we screened receptor tyrosine kinase (RTK) inhibitors for anti-EBOV activity by using our previously established biologically contained Ebola virus that lacks the VP30 gene (EBOVΔVP30) and identified several RTKs, including human epidermal growth factor receptor 2 (HER2), as potential targets of anti-EBOV inhibitors and as novel host factors that have a role in EBOV infection. Of these identified RTKs, it was only HER2 whose knockdown by siRNAs impaired EBOVΔVP30-induced AKT1 phosphorylation, an event that is required for AKT1 activation and subsequent macropinocytosis. Stable expression of HER2 resulted in constitutive activation of AKT1, resulting in the enhancement of EBOVΔVP30 growth, EBOV GP-mediated entry, and macropinocytosis. Moreover, we found that HER2 interacts with the TAM receptors, and in particular forms a complex with TYRO3 and EBOVΔVP30 particles on the cell surface. Interestingly, HER2 was required for EBOVΔVP30-induced TYRO3 and AKT1 activation, but the other TAM receptors (TYRO3 and MERTK) were not essential for EBOVΔVP30-induced HER2 and AKT1 activation. Our findings demonstrate that HER2 plays an important role in EBOV entry and provide novel insights for the development of therapeutics against the virus.